Implication of Juvenile Delinquents to the Community: Basis for Social Reintegration Program: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Juvenile delinquency is one of the greatest problems in our society today. There are primaryreasons why young people start to rebel at a young age, and that sometimes puts them inserious situations. The behavior of a child is first developed at home. So, what they first adoptat home is what they will show and apply to the community. The reintegration of juveniledelinquents into the community promotes accepting the child back into the community afterbeing sent to youth centers and detention centers to rehabilitate and go through counselingservices. The juvenile delinquents are taking a step to demonstrate to the community that theyare capable of changing their undesirable behavior into something positive and sociallyacceptable. The researchers conclude that in order to avoid or lessen the increase in thepopulation of juvenile delinquents and the discrimination by the community, it is necessary toconduct seminars and programs in every barangay that focus on the topic of juveniledelinquency and its effects that will benefit not only the youth but also their families and thecommunity.
Keywords: Criminology